Anticonvulsant effects of carbon dioxide and hypoxia (Revista Española de Fisiología, 1960)
After a bibliographic review, in which we have found un- certain problcms and aspects not yet stated, we have seen that experimental research on hypoxia and hypercapnia with regard to the convulsión liave not been guided by the way of clinical application of the results. Consequently, we have begun our experimental works on the effect of hj'poxia and hypercapnia in order to search out some methods which should allow a possible routinary clinical use in electroencephalographic diag nosis. On these paper, results and our first observations on ex perimental animáis are reported.In the experimental study unanesthetized guinea-pigs were used with controled artificial respiration by the Starling’smethod. The EKG, and EEG with electrodes screwed in the perforated skull in contact with dura, were simultaneously recorded by means of ten channel Insel electroencephalo- graph. Metrazol was given i. v. in 80 mg/kg. doses. Thisexcessive doses was used to reach convulsive response in all cases independently of the individual variabilitj’- to thethreshold doses. In order to avoid the muscular phenomenous, d-tubocurarine, which lacks of cerebral effects, was injected to the animáis.In order to study the effect on convulsions, animáis were exposed to atmospheres of variable C02 concentrations. Inhala- tion of 12-14-25 and 30 % CO2 in O2 and air were used. Inhalation of 100 % CO2 during a very short time was also used.Inhalation of 12-15 % CO2 in O2. On these concentrations we did not find sensibly modifications of electric cerebral ac- tivity of background in the curarized animal at least during 20 minutes of inhalation. Frecuency and morphology of the EKG are neither ostensibly disturbed. These concentrations in crease metrazolic threshold but do not prevent the repeated seizures. However, these seizures are shortened in time, de- creased in number and change its electric expression.This gas mixture (12-15 % CO2) eliminates the abnormal potentials which could appear by cortical acute injury when the employment of electrodes is unable. Likewise, it recovers aproximately as background activity the slowness and hyper- synchrony brought out when the animal is submited to conse- cutive episodes of apnea (fig. 1, 2, 3, 4 and 5).Inhalation of CO2 in air at the same concentration (12-15 % O2) carries to similar results than of those mixture CO2 in O* if to the gas mixture of CO2 in air, O2 is added until it reaches approximately 24 %.Inhalation of 20 % CO2 in O2. — Prolonged respiration of this concentration originales light bradycardia without mor- phologic changos of the EKG. Metrazol i. v. (80 mg/kg) placing